Spatial patterns of bat diversity overlap with woodpecker abundance - Kotowska,Dorota; Zegarek,Marcin; Osojca,Grzegorz; Satory,Andrzej; Pärt,Tomas; Żmihorski,Michał (PeerJ, 2020)
Woodpecker diversity is usually higher in natural forests rich in dead wood and old trees than in managed ones, thus this group of birds is regarded as an indicator of forest biodiversity. Woodpeckers excavate cavities which can be subsequently used by several bird species. As a consequence, their abundance indicates high avian abundance and diversity in forests. However, woodpecker-made holes may be also important for other animals, for example, mammals but it has seldom been investigated so far. Here, we examine how well one species, the Great Spotted Woodpecker, predicts species richness, occurrence and acoustic activity of bats in Polish pine forests. In 2011 we conducted woodpecker and bat surveys at 63 point-count sites in forests that varied in terms of stand age, structure and amount of dead wood. From zero to five Great Spotted Woodpeckers at a point-count site were recorded. The total duration of the echolocation calls during a 10-min visit varied from 0 to 542 s and the number of bat species/species groups recorded during a visit ranged between zero to five. The local abundance of the woodpecker was positively correlated with bat species richness (on the verge of significance), bat occurrence and pooled bat activity. The occurrence of Eptesicus and Vespertilio bats and Nyctalus species was positively related with the abundance of the Great Spotted Woodpecker. The activity of Pipistrellus pygmaeus, Eptesicus and Vespertilio bats and a group of Myotis species was not associated with the woodpecker abundance, but echolocation calls of Nyctalus species, P. nathusii and P.pipistrellus were more often at sites with many Great Spotted Woodpeckers. Moreover, the probability of bat presence and the activity of bats was generally higher shortly after dusk and in middle of the summer than in late spring. We suggest that the observed correlations can be driven by similar roosting habitats (e.g., woodpeckers can provide breeding cavities for bats) or possibly by associated invertebrate food resources of woodpeckers and bats. The abundance of Great Spotted Woodpecker seems to be a good positive indicator of bat species richness, occurrence and activity, thus adding a group of relatively cryptic forest species that are indicated by the presence of the Great Spotted Woodpecker.
Keywords: Bat communities; Dendrocopos major; Indicator species; Managed forest; Windthrow